Aggressive angiomyxoma of the vulva - a rare entity: case report and review of literature - Gaurav, Amrita; Gill, Poonam; Khoiwal, Kavita; Chowdhuri, Sandipan; Kapoor, Dhriti; Chaturvedi, Jaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Aggressive angiomyxoma (AA) is an extremely rare locally invasive mesenchymal tumor with a high risk of recurrence. Till date, only about 350 cases reported worldwide. Because of the rarity it should be considered as differential diagnosis whenever patient present with vulvovaginal growth. The diagnosis is clinched on histopathology. These are hormone-dependent and have estrogen and progesterone receptors. Hence sometimes GnRH agonists are used for ovarian estrogen secretion suppression but long-term use is not advocated due to side effects. A 45-year-old P4 L4 perimenopausal female presented to the GOPD with a 4×4×3 cms pedunculated painless globular mass on right labia majora. On palpation, the globular mass was firm, non-tender and with a smooth surface. Mass was excised and on gross histopathology, cut sections showed white myxoid areas. On microscopy epidermal lined tissue with stellate and spindle-shaped mesenchymal cells was found, embedded in a loose myxoid stroma with few collagen fibers. The cells were small and bland and lacked nuclear atypia. Small to medium-sized blood vessels were present with the thickened wall. Entrapped nerves and adipocytes were also present. No necrosis or mitosis was identified. All these features were suggestive of an aggressive angiomyxoma. Immunohistochemistry markers ER, PR, CD34, desmin, SMA were all positive. Imaging was done to rule out metastatic lesions and wide local excision was done around the stump with laparoscopic bilateral oophorectomy. Aggressive angiomyxoma is a rare disease. In women with asymptomatic growth in the vulvovaginal region, perineum or pelvis, aggressive angiomyxoma should be considered as a differential diagnosis. Ideal treatment is a wide local excision to prevent local recurrences, which are common and a hypoestrogenic milieu is created by either GnRH Agonists or by bilateral oophorectomy due to their hormone-sensitive nature.